The place's manifestations in "Dreams of Blood Times" by Djamel Foughali - Ouldji, Biya (Journal of Human Sciences, 2021)
The objective that this study aims to achieve is an attempt to fig&ure an element of the narrative work which is the place, which is one of the basic components in the narrative construction and to explore its importance and types for the narrator "Jamal FOUGHALI". The place is a part of the narrative fabric. In general its importance is in the narrative cohesion.